Qoraqalpoq Musiqa Uslubi O`Ziga Yarasha Xilma-Xil Va Rang-Barangligi - Turdiev Qalbay Abievich (Miasto Przyszłości, 2023)
Karakalpak musical styles are based on the household economy of people’s lives, geographical features of the region and formation in the process of direct socio-historical development. If you pay attention to their musical genres, they are also very diverse, especially in the style of " Jirov bakhshilik" has a special place.